The Jujuran Tradition Among the Banjar Community in Kapuas Regency And its Impact on the Intention to Marry from an Islamic Law Perspective - Shofia Ihsani Azizah; Ruston Kumaini; Ahmad Muslihuddin (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
The jujuran tradition is a pre-marital practice among the Banjar community that carries social, cultural, and economic values in community life. This study aims to analyze the practice of the jujuran tradition in Banjar marriages in Kapuas Regency from social and cultural perspectives, its impact on marriage intention, and its assessment within Islamic legal thought. This research employs a qualitative approach using field research methods. Data were collected through in-depth interviews, observation, and literature review, and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings show that jujuran serves economic, social, and symbolic functions within the Banjar community. Socially, it strengthens relationships between families, while economically it reflects financial readiness for marriage. However, the practice of jujuran also has an ambivalent impact on marriage intention, as it can function both as motivation and as a barrier. At a proportional level, jujuran encourages marital readiness, but when the amount is excessively high, it may delay or even hinder marriage due to economic limitations. From the perspective of Islamic law, jujuran can be classified as ‘urf shahih as long as it does not contradict Sharia principles, particularly in promoting public welfare and avoiding hardship for those intending to marry. Therefore, the continuity of the jujuran tradition should be managed proportionally to ensure that it remains in harmony with customary values and Islamic legal principles.